Germline Polymorphisms in the Nuclear Receptors PXR and VDR as Novel Prognostic Markers in Metastatic Colorectal Cancer Patients Treated With FOLFIRI - De Mattia, Elena; Polesel, Jerry; Roncato, Rossana; Labriet, Adrien; Bignucolo, Alessia; Dreussi, Eva; Romanato, Loredana; Guardascione, Michela; Buonadonna, Angela; D'Andrea, Mario; Lévesque, Eric; Jonker, Derek; et al. (Frontiers in Oncology, 2019)
Nuclear receptors act as mediators of cancer-related inflammation and gene expression. They have a regulatory effect on genes encoding proteins related to drug adsorption, distribution, metabolism, and excretion. The aim of the present study was to highlight novel prognostic markers among polymorphisms in genes encoding for nuclear receptor proteins and inflammation-related cytokines in patients treated with a FOLFIRI regimen. This study included two independent cohorts comprising a total of 337 mCRC patients homogeneously treated with first-line FOLFIRI. Genotyping of 246 haplotype-tagging polymorphisms in 22 genes was performed using bead array technology. The NR1I2 (PXR)-rs1054190 and VDR-rs7299460 polymorphisms were significantly associated with patient overall survival (OS). A detrimental effect of the NR1I2 rs1054190-TT genotype on OS was observed in both the discovery and replication cohorts (HR=6.84, P=0.0021, q-value=0.1278 and HR=3.56, P=0.0414, respectively). Patients harboring the NR1I2 rs1054190-TT genotype had a median OS of 9 months vs. 21 months in patients with C-allele (P<0.0001 log-rank test). VDR rs7299460-T was consistently associated with a longer OS in both cohorts (discovery: HR=0.61, P=0.0075, q-value=0.1535; replication: HR=0.57, P=0.0477). Patients with the VDR rs7299460-T allele had a median OS of 23 months compared to 18 months in those with the CC genotype (P=0.0489, log-rank test). The NR1I2-rs1054190 polymorphism also had an effect on the duration of progression-free survival, consistent with the effect observed on OS. Two novel prognostic markers for mCRC treated with FOLFIRI were described and, if validated by prospective trials, have a potential application in the management of these patients